Small bowel obstruction caused by hiatal hernia - Jacob Cabrejas; Kara Zweerink; Wesley Eilbert (JEM Reports)
Background: A hiatal hernia is caused by herniation of a portion of the stomach or other abdominal viscera into the thorax through the esophageal hiatus of the diaphragm. It is a common condition and asymptomatic in most cases. Case report: We present the case of a 52-year-old male with a past medical history of previous hiatal hernia repair who presented to the emergency department with one day of diffuse abdominal pain and multiple episodes of emesis. Bowel sounds were heard on auscultation of his left chest. Computed tomography of the abdomen and pelvis demonstrated multiple abdominal contents herniating through the esophageal hiatus. Multiple dilated loops of small bowel were seen in the left hemithorax with decompressed small bowel seen more distally, indicating a small bowel obstruction with a transition point in the thoracic cavity.Why should an emergency physician be aware of this? Hiatal hernia is a common condition. While rare, large hiatal hernias may result in herniation of small bowel with the potential complication of bowel obstruction.